HUBUNGAN MOTIVASI DENGAN PERILAKU PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS KOTAKALER SUMEDANG UTARA - Dirgahayu, Inggrid; Dewi, Shania Octavia; Jayanti, Tri Nur (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Cervical cancer is a cancer that takes many lives of women. The Indonesian Ministry of Health in 2015 reported that there were 200,000 deaths due to cervical cancer, 46,000 of them were eligible women. Delaying in early detection is the cause of death for cervical cancer patients. This is happened due to a lack of motivation to carry out VIA medical examinations such as intrinsic motivation and extrinsic motivation. The purpose of this study is to determine the relationship between motivation and the behavior of the Visual Inspection of Acetic Acid (VIA) medical examinations in eligible women in the Kotakaler Health Center, North Sumedang. This research is a correlative research with case control design. The population in this study were 1198 eligible women who were married. The sampling technique used consecutive sampling which obtained 46 case groups and 46 control groups. The instrument used was questionnaire. Analysis of the data used is the Chi-Square test with α <0.05.The results of statistical tests obtained the value p = 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected. This that there is relationship between motivation and the behavior of the Visual Inspection of Acetic Acid (VIA) medical examinations in eligible women in the Kotakaler Health Center, North Sumedang. Community nurses Provide health education to increase their motivation in early detection of cervical cancer using the VIA method.